Role of energy consumption, tourism and economic growth in carbon emission: evidence from Kuwait - Aarif Mohammad Khan; Uzma Khan; Sana Naseem; Shaha Faisal (Cogent Economics & Finance, 2023)
Even though the Paris Agreement and the Sustainable Development Goals say that low-carbon economic growth is essential, more research must be done to determine how the tourism sector affects carbon productivity. So, to see if increased energy usage, tourism, and economic growth jointly raise carbon productivity in Kuwait, this study uses a vector error correction strategy to look at the years 1995-2020. Predictions about how sustainable tourism will affect energy efficiency, and carbon productivity improvements are also an excellent way to learn more about this subject. As the amount of carbon dioxide in the air increases, tourism will go down by 0.13 percent. Inverse cointegration is the term for this phenomenon. However, the vector error correction model showed that carbon emissions go down as the economy grows and people pay more attention to how much energy they use. Nevertheless, Granger's theory of cause and effect says that carbon emissions, energy use, and economic growth can only lead to more tourism in one way.
Keywords: 330; Carbon emissions; economic growth; energy use; Kuwait; VECM